Reliability-based economic model predictive control for generalised flow-based networks including actuators` health-aware capabilities - Grosso, Juan M.; Ocampo-Martinez, Carlos; Puig, Vicenç (Zielona Góra: Uniwersytet Zielonogórski)
This paper proposes a reliability-based economic model predictive control (MPC) strategy for the management of generalized flow-based networks, integrating some ideas on network service reliability, dynamic safety stock planning, and degradation of equipment health. The proposed strategy is based on a single-layer economic optimisation problem with dynamic constraints, which includes two enhancements with respect to existing approaches.
Keywords: model predictive control; flow-based networks; dynamic safety stocks; actuator health; service reliability; chance constraints; economic optimisation